(untitled) (Doctor Virtualis, 2022)
The modern rediscovery and re-appropriation of Ibn Khaldūn’s work by Arab scholars has largely developed along the following dichotomy. On the one hand, some have described Ibn Khaldūn as an original and atypical thinker for his context and time, and as the only or highest representative of Arab-Islamic thought – thus partly reinforcing the view of many Western scholars who had minimized the role of the tradition to which he belonged. On the other hand, there has been an opposite trend that demotes his originality, by highlighting his complete adherence to the Islamic tradition of historiography and thought. This contribution studies four prominent contemporary Moroccan scholars who have systematically addressed Ibn Khaldūn’s philosophy: Mohammed Aziz Lahbābi, Mohammed Abed al-Jābrī, Abdallah Laroui, and Bensalem Himmich. The essay first considers Lahbābi and al-Jabri, Lahbābi’s most renowned pupil; the former due to his contribution to the advancement of the study of Ibn Khaldūn in general, and as one of the founders of the school of Rabat, and the latter due to the theoretical importance and systematic nature of his critical approach to Arab thought. Laroui, another representative of the school of Rabat, offers an analysis which highlights different characteristics of Ibn Khaldūn’s work, compared to the first two scholars, by focusing on the subjects of modernity and the State. Finally, the chapter examines Himmich’s reading. Himmich has written both an academic work as well as a literary/fictional biography of the Maghrebi figure in focus. All these four scholars have made a substantial impact on the Arab world, whilst also being wellknown in the West, Laroui in particular.